BASALE SIRIH LAYANG NGUBAT REVITALISASI UPACARA BASALE PADA SUKU ANAK DALAM - Nopiansyah, Radius (LP2M ISBI Bandung, 2015)
Basaleis name ofthe ritual of Anak Dalam Tribe in Jambi. There are some function soft his ritual, such as wedding ceremony, santet (local voodoo ), and medication. Since1978, their Basale's medication ceremony is developed to an art performance without losing its sanctity named Basale Sirih Layang Ngubat. This performance has been developed by Darwan Asri with Maliki (Alm.), one of the leaders of Anak Dalam Tribe in Batanghari Regency of Jambi